Substrate multispecificity among 20β-hydroxysteroid dehydrogenase type 2 members. (15th June 2020) - Tokarz, Janina; Lintelmann, Jutta; Möller, Gabriele; Adamski, Jerzy
Abstract: Steroids regulate many physiological processes. Hydroxysteroid dehydrogenases (HSDs) modulate the levels of steroids in pre- and post-receptor metabolism. The subfamily of 20β-HSD type 2 currently comprises six members from six different species. The zebrafish ortholog converts cortisone to 20β-dihydrocortisone and is involved in the catabolism of the stress hormone cortisol. Here, we elucidated the substrate preferences of all 20β-HSD type 2 enzymes towards a selected panel of steroids. For quantification of the substrates and their respective 20β-reduced products, we first developed and validated a liquid chromatography-mass spectrometry based method. Applying this method to activity assays with recombinantly expressed enzymes, our findings indicate that the 20β-HSD type 2 enzymes catalyze the 20β-reduction of a plethora of steroids of the glucocorticoid biosynthesis pathway. The observed multispecificity among the homologous 20β-HSD type 2 enzymes implies different physiological roles in different species. Highlights: LC-MS/MS method capable of quantifying 19 steroids. Baseline separation of 20α- and 20β-isomers of glucocorticoids. 20β-HSD type 2 enzymes catalyze the 20β-reduction on a plethora of steroids. Enzyme multispecificity implies different physiological roles in different species.